Doing family therapy : craft and creativity in clinical practice - Taibbi, Robert
"Featuring rich case examples, this book has helped tens of thousands of students and therapists build the skills and confidence needed to tackle the full range of issues that families bring to therapy. Rather than advocating one best approach, Robert Taibbi shows that there are multiple ways to guide families and harness their strengths. The book maps out the challenges and process of the beginning, middle, and end stages of treatment; presents creative strategies for assessment and intervention with parents and kids of all ages; analyzes how working with individuals can effect helpful changes in couples and families; and offers practical tips for overcoming common roadblocks. End-of-chapter reflection questions and experiential exercises encourage readers to develop their own clinical style. New to This Edition *Reflects the author's clinical experience and recent advances in the field. *Extensively revised chapter on core concepts: process, patterns, problems, and resistance. *More detailed recommendations for conducting the first session and doing assessments. *Quick-reference guidelines for treating frequently encountered adolescent problems. See also the author's Doing Couple Therapy: Craft and Creativity in Work with Intimate Partners"--